Higher Education Students’ Perceptions of Using English Songs for Vocabulary Development - Maylani Ayu Wulandari; Daud Jiwandono (Universitas Pahlawan Tuanku Tambusai, 2026)
Vocabulary development is fundamental to English language learning, yet conventional instructional methods often limit learner engagement and long-term retention. Although English songs have been widely explored as an alternative learning medium, previous studies have primarily emphasized vocabulary achievement rather than higher education students' perceptions and the challenges they experience. Therefore, this study aimed to explore undergraduate students' perceptions of using English songs for vocabulary development and identify the challenges they encountered during the learning process. This study employed a descriptive survey design with a mixed-methods approach, integrating quantitative and qualitative data. Data were collected from 42 undergraduate students through an online questionnaire consisting of Likert-scale items and open-ended questions. The quantitative data were analyzed using descriptive statistics, while the qualitative responses were examined through thematic analysis. The findings revealed overwhelmingly positive perceptions across all indicators, including vocabulary acquisition, contextual understanding, pronunciation awareness, vocabulary retention, and learning motivation. However, students also reported challenges related to fast-paced lyrics, pronunciation variations, unfamiliar vocabulary, and slang expressions. These findings suggest that English songs are an effective resource for vocabulary development, particularly when accompanied by structured vocabulary-focused learning activities that help students engage more meaningfully with authentic language input.